اﻟﺗوزﯾﻊ اﻟﺟﻐراﻓﻲ ﻟﻣﺣﺻول اﻟذرة اﻟﺻﻔراء ﻓﻲ ﻣﺣﺎﻓظﺔ واﺳط (i)(٢٠١٠– ٢٠٠٣ )ﻟﻠﻣدة )ﺑﺣث ﻣﺳﺗل ﻣن رﺳﺎﻟﺔ ﻣﺎﺟﺳﺗﯾر( (Journal of the College of Education for Women, 2019)
This study focuses on the basics and the details of production of maize in Wasit province, in order to detect the spatial variation of the cultivation, production and the reality of their geographical distribution. The study has shown that maize is an important field crops grown in this province. The research found many conclusions, including the following: (1) The top area had been planted with maize in Wasit province, was (102888) acres with a total standard degree (Sd) scored at (1.3), in 2004; while the lowest planted area, namely, (43196) acres was planted in 2010 with a standard degree of (-1.6). The rate for the space across the province during the study period amounted to (75456) acres. . (2) The highest rate for the area of cultivated with maize appeared in areas of reclaimed land, such as the districts of Al-Numaniya and Al-Saouira, as the rate of space were (28234 and 24530) acres respectively; while the districts of Al-Kut and Badra were at low levels ofaverageareaof (7259 and 1293) acres, respectively. (3) With respect to production rates, due to higher yields per dunum, the district of AlSaouira was in the first place, with a rate of production (14418) tones; Al-Numaniya, came second with a rate of production of (10896) tons. The reasons for low production in the rest of the districts was attributable to water scarcity and low selling prices compared with the costs of production, which led to the reluctance of farmers for cultivation. (4) The highest rate of productivity was achieved in the district of Al-Saouira, reaching at (588) kg/acre, particularly in the sub-district of Al-Shihimih (674 kg/acre). The district of Al-Azizia came in the second place with an average of (574) kg/acre, especially in the center of the district (651 kg/acre). The less productivity per acre that has been cultivated with maize has observed in the district of Badra, amounting to (254) kg / sq.m. (5) With regard to the rates of fluctuation in the cultivated areas, quantities of production and productivityofmaize:thelowestvolatilitywas observed in Al-Azizia district,as itamounted to(17.8)%; whilethehighestvolatilitywas in the sub-district ofAl-Shihimih, as itamounted to(75.9%).